Fragile X–Associated Tremor/Ataxia Syndrome: Influence of the FMR1 Gene on Motor Fiber Tracts in Males With Normal and Premutation Alleles - Wang, Jun Yi (2013)
IMPORTANCE: Individuals with the fragile X premutation express expanded CGG repeats (repeats 55–200) in the FMR1 gene and elevated FMR1 messenger RNA (mRNA) levels, both of which may underlie the occurrence of the late-onset neurodegenerative disorder fragile X–associated tremor/ataxia syndrome (FXTAS). Because the core feature of FXTAS is motor impairment, determining the influence of FMR1 mRNA levels on structural connectivity of motor fiber tracts is critical for a better understanding of the pathologic features of FXTAS. OBJECTIVE: To examine the associations of CGG repeat and FMR1 mRNA with motor-related fiber tracts in males with premutation alleles. DESIGN AND SETTING: A case-control study conducted at the University of California, Davis, from April 1, 2008, through August 31, 2009. All data were collected masked to the carrier status of the FMR1 gene. PARTICIPANTS: Thirty-six male premutation carriers with FXTAS and 26 male premutation carriers without FXTAS were recruited through their family relationships with children affected by fragile X syndrome. The controls were 34 unaffected family members and healthy volunteers from the local community. MAIN OUTCOMES AND MEASURES: The CGG repeat lengths and FMR1 mRNA expression levels in peripheral blood lymphocytes, motor functioning, and white matter structural integrity that were estimated using diffusion tensor imaging. After data collection, we selected 4 motor tracts to reconstruct using diffusion tensor tractography, namely, the middle and superior cerebellar peduncles, descending motor tracts (containing the corticospinal, corticobulbar, and corticopontine tracts), and the anterior body of the corpus callosum. RESULTS: All fiber tracts exhibited weaker structural connectivity in the FXTAS group (decreased 5%–53% from controls, P ≤ .02). Genetic imaging correlation analysis revealed negative associations of CGG repeat length and FMR1 mRNA with connectivity strength of the superior cerebellar peduncles in both premutation groups (partial r(2) = 0.23–0.33, P ≤ .004). In addition, the measurements from the corpus callosum and superior cerebellar peduncles revealed a high correlation with motor functioning in all 3 groups (r between partial least square predicted and actual test scores = 0.41–0.56, P ≤ .04). CONCLUSIONS AND RELEVANCE: Distinct pathophysiologic processes may underlie the structural impairment of the motor tracts in FXTAS. Although both the corpus callosum and superior cerebellar peduncles were of great importance to motor functioning, only the superior cerebellar peduncles exhibited an association with the elevated RNA levels in the blood of fragile X premutation carriers.